Proceedings of the 2010 ACM Conference on Computer Supported Cooperative Work 2010
DOI: 10.1145/1718918.1718925
|View full text |Cite
|
Sign up to set email alerts
|

Social language network analysis

Abstract: In this note we introduce a new methodology that combines tools from social language processing and network analysis to identify socially situated relationships between individuals, even when these relationships are latent or unrecognized. We call this approach social language network analysis (SLNA). We describe the philosophical antecedents of SLNA, the mechanics of preprocessing, processing, and post-processing stages, and the results of applying this approach to a 15-month corporate discussion archive. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…The present study, however, does extend and conceptually replicate these earlier findings on social dominance by showing that physicians with higher levels of implicit racial bias also tend to use personal pronouns that prior research (Dino et al, 2009; Hancock et al, 2010; Scholand et al, 2010) has found to be associated with assumed higher status in interpersonal interactions. We believe this conceptual replication is theoretically important and casts more light on what exactly physicians with higher levels of implicit racial bias are doing to make their patients see them as less patient-centered and trustworthy (Blair et al, 2013; Cooper et al, 2012; Haussmann et al, 2015; Penner et al, 2013).…”
Section: Limitationssupporting
confidence: 74%
See 2 more Smart Citations
“…The present study, however, does extend and conceptually replicate these earlier findings on social dominance by showing that physicians with higher levels of implicit racial bias also tend to use personal pronouns that prior research (Dino et al, 2009; Hancock et al, 2010; Scholand et al, 2010) has found to be associated with assumed higher status in interpersonal interactions. We believe this conceptual replication is theoretically important and casts more light on what exactly physicians with higher levels of implicit racial bias are doing to make their patients see them as less patient-centered and trustworthy (Blair et al, 2013; Cooper et al, 2012; Haussmann et al, 2015; Penner et al, 2013).…”
Section: Limitationssupporting
confidence: 74%
“…Turning to social psychology research of linguistic patterns, extensive research has shown that social dominance and/or status is strongly associated with use of first-person pronouns. Specifically, higher status speakers tend to use more first-person plural pronouns (e.g., we, us, our) and less first-person singular pronouns (e.g., I, me, my; Dino, Reysen, & Branscombe, 2009; Hancock et al, 2010; Scholand, Tausczik, & Pennebaker, 2010). For example, a study of triads during flight simulations showed that as rank went up (i.e., second lieutenant, first lieutenant, and captain), the use of first-person plural pronouns also increased (Sexton & Helmreich, 2000).…”
Section: Racial Bias Social Dominance and Use Of First-person Pronounsmentioning
confidence: 99%
See 1 more Smart Citation
“…Marginal, low status members tend to use singular pronouns, such as "I," rather than collective pronouns, such as "we," because they lack standing in the group, gain esteem from their personal identity, and tend to have a self-focus (Brewer & Gardner, 1996;Jetten, Branscombe, Spears, & McKimmie, 2003;Kacewicz, Pennebaker, Davis, Jeon, & Graesser, 2014;Rink & Ellemers, 2011). This result has been found in emails and letters between high and low status group members Kacewicz et al, 2014), in online forum discussion groups (Dino, Reysen, & Branscombe, 2009;Reysen, Lloyd, Katzarska-Miller, Lemker, & Foss, 2010), in airplane crews (Krifka, Martens, & Schwarz, 2003;Sexton & Helmreich, 2000), in discussions among doctors, patients, and companions (Sakai & Carpenter, 2011), in long-term online collaboration (Scholand, Tausczik, & Pennebaker, 2010b), and in the conversations of ad hoc laboratory groups (Kacewicz et al, 2014). Low status group members may be more self-focused or may be trying to call attention to themselves to gain visibility from higher status members.…”
Section: Group Inputs Reflected In Language Usementioning
confidence: 91%
“…Third, researchers can ask participants to provide anonymized e-mails when practical (e.g., Kacewicz, Pennebaker, Davis, Jeon, & Graesser, 2014). For larger scale analyses, automating the analysis of deidentified electronic communication (e.g., via word-count software or social language network analysis; e.g., Scholand, Tausczik, & Pennebaker, 2010) rather than using human coders is likely to pass most ethical standards.…”
Section: Practical Suggestions For Researchmentioning
confidence: 99%